1983
DOI: 10.1017/s0033291700051552
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial intervention with cancer patients: a review

Abstract: SynopsisIt is well established that a diagnosis of cancer and the subsequent treatment can cause a great deal of stress, and the need for psychosocial support is increasingly being advocated. The data for the efficacy of intervention programmes are reviewed. The evidence relating to the benefits gained by patients is equivocal. The indication is that a selective rather than a blanket service is needed, with the target for intervention being patients at high risk for psychological morbidity. The advantages of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 27 publications
0
43
0
2
Order By: Relevance
“…However, psychosocial intervention is not necessarily total and psychosocial dimension of SIP were lower in beneficial and may even accentuate distress in the than at the 3-month follow-up. Perception by a patient that stresses of adverse events may be beyond control process of trying to change psychological responses [4]. The design of the programme is therefore important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, psychosocial intervention is not necessarily total and psychosocial dimension of SIP were lower in beneficial and may even accentuate distress in the than at the 3-month follow-up. Perception by a patient that stresses of adverse events may be beyond control process of trying to change psychological responses [4]. The design of the programme is therefore important.…”
Section: Discussionmentioning
confidence: 99%
“…Many such programmes have been tried in patients the diagnosis, accept recommended treatment and adapt to sequelae of extensive ablative surgery. Even when with cancer [4], individually or in groups, with the type of support possibly determined by the availability of staÂ. apparently cured, diÃculties can arise from stomal or parastomal complications, leakage or diÃculty in emptyAs a rule, the programme is begun immediately after the diagnosis of cancer, to inform on diagnosis, treatment ing urine, and emotional and sexual problems.…”
Section: Introductionmentioning
confidence: 99%
“…Citations in identified papers and reviews (Watson, 1983;Cunningham, 1988;Vachon, 1988;Harman, 1991;Andersen, 1992;Trijsburg et al, 1992), Aslib. index to theses (keywords cancer, counselling and psychotherapy), and Comprehensive Dissertation Abstracts: Psychology (keyword cancer) were manually searched.…”
Section: Search Strategymentioning
confidence: 99%
“…Several studies have also shown that cancer patients may benefit from psychological interventions (Watson, 1983;Andersen, 1992, Trijsburg et al, 1992. The use of cognitiveÐbehavioural techniques is well established for the treatment of both anxiety and depression in cancer patients (Greer et al, 1992;Fawzy et al, 1993;Watson et al, 1996).…”
mentioning
confidence: 99%